Photosynthetic and transcriptional responses of the marine diatom Thalassiosira pseudonana to the combined effect of temperature stress and copper exposure. Issue 2 (30th November 2017) - Leung, Priscilla T.Y.; Yi, Andy Xianliang; Ip, Jack C.H.; Mak, Sarah S.T.; Leung, Kenneth M.Y.
Abstract: A 96-h exposure experiment was conducted to elucidate the toxicity responses of the marine diatom Thalassiosira pseudonana upon exposure to different temperatures and copper (Cu) concentrations. Three Cu treatments (seawater control; 200 μg/L Cu, EC50 for the yield at 25 °C; and 1000 μg/L Cu, EC50 for growth inhibition at 25 °C) were conducted against four temperatures (10 °C, 15 °C, 25 °C and 30 °C). Growth rate and photosynthetic responses showed a significant interacting thermal-chemical effect with strong synergistic responses observed at 30 °C treatments. Expression of heat shock protein ( hsp ) was positively modulated by increasing temperatures. Hsp 90, hsp90–2 and sit1 (related to silica shell formation) were highly expressed at 30 °C under 1000 μg/L Cu, while the genes encoding light harvesting proteins ( 3HfcpA and 3HfcpB ) and silaffin precursor sil3 were significantly up-regulated at 15 °C under 200 μg/L Cu. Our results indicated an increase Cu toxicity to T. pseudonana under high temperature and Cu dose. Highlights: We examined the combined effect of temperature and copper (Cu) to a marine diatom. Cu toxicity to T. pseudonana was synergistic under high temperature and Cu level. We reported a profound toxic effect on growth of the diatom. Heat shock proteins in T. pseudonana were generally regulated by temperature effect. We reported a treatment of low Cu level at 15 °C promoted photosynthesis and shell formation process.